THE LINGUISTIC STRATEGIES DIFFERENCES BETWEEN MEN AND WOMEN POST GRADUATE STUDENTS OF ENGLISH EDUCATION PROGRAM OF UNDIKSHA SINGARAJA - Dewi, Komang Trisna (Yavana Bhasha : Journal of English Language Education, 2019)
This study focused on the analysis of linguistic strategies differences between men and women which was to investigate the linguistic strategies applied by male and female post graduate students of the English Education Program of UNDIKSHA Singaraja. This study was designed by using descriptive qualitative approach in which the data collected were analyzed qualitatively. The researcher acted as non-participant observer in which the data were gathered by recording the conversation done. The result of the data analysis showed that the data show that during the daily conversation, it can be found that the linguistic strategies applied by both male and female speakers. They use this kind of strategy in order to express their opinion or feeling. Moreover, from those conversations, the data which was related to the strategies was got. Based on data, it can be concluded that male and female post graduate students of the English Education Program of UNDIKSHA Singaraja, differ in applying linguistic strategies during their daily conversation. In having a conversation, men interrupt more than women and women show their silence response more often in their conversation rituals. Moreover, in raising the conversation topic, both men and women have different topic to be talked about. Men tend to speak about something which can put them in competitive situation, such as game whereas women tend to speak about something that can make them stand in the middle of solidarity, such as feelings. Besides, men also use indirectness to convey something that can low their status but women use indirectness because they felt they had lower status than men and they wanted to get pleasant experience of getting one’s way not because one demands it (power) but because the other person wants the same thing (solidarity).